Image and Poetic Imagination in the Book of Malaga notables - Ahmed, Basil Saleh; Yousef, Juma Hussein (Journal of Ecohumanism, 2025)
This study explores the interplay of image and poetic imagination in The Book of Málaga Notables, focusing on how the text employs vivid imagery and evocative language to encapsulate the cultural, historical, and artistic identity of Málaga, Spain. Through the lens of poetic imagination, the work transcends mere documentation, transforming the lives and contributions of Málaga’s notable figures into a rich tapestry of metaphor, symbolism, and aesthetic expression. Key themes include the reimagining of historical and cultural narratives, the fusion of tangible and intangible heritage, and the evocation of place as a living, breathing entity. The analysis highlights the book’s ability to intertwine the factual with the poetic, offering readers an immersive journey that bridges the real and the imaginative, thereby elevating Málaga’s legacy into a realm of timeless artistic resonance.